A compact wide beamwidth dual‐polarized antenna for 5G new radio. Issue 5 (8th February 2022) - Feng, Yunxia; Zhang, Fu‐Shun; Guan, Yunjie; Xie, Guo‐Jun; Yuan, Hong; Zhang, Fan
Abstract: In this article, a compact wide beamwidth dual‐polarized antenna is proposed and experimentally investigated. The operating frequency band of the antenna presented in this article is 3.29–5.28 GHz, covering n77, n78, n79 frequency bands of the 5G new radio (NR) bands. The stable wide beamwidth radiation pattern is obtained by encircling a metal wall around the traditional metal flat floor. Furthermore, the bandwidth of the antenna is improved by using the metal wall with grooves and trapezoidal parasitic elements. With these rectangular grooves, the dimensions of the antenna presented in this article are decreased. The impedance bandwidth of the antenna is 46.4% (| S 11 | ≤ –10 dB). The isolation between the two ports is higher than 22 dB in 3.29–5.28 GHz. The half‐power beamwidths of the H‐plane and the E‐plane are greater than 110° and 102° in 3.3–5.0 GHz, respectively.